Tanggung Jawab Developer Terhadap Perjanjian Jual Beli Dalam Pengadaan Perumahan - Nur Aisyah, Siti; Anzila Mafaza; Zulfi Aini; Helfira Citra (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2024)
Currently, when talking about responsibility, there are many cases are found between consumers and developers which are caused by the developer’s irresponsibility, changes to building specifications and other breaches of contract. In practice, in housing sale and purchase agreements, consumers are often placed in a marginal position so that the applicable agreement is often detrimental to the consumer. The developer’s responsibility in the agreement ends after the contruction of the house in question is completed. Problems can arise when the specifications of the agreed house do not match the contents of the agreement. So this article aims to analyze the developer’s responsibilities in implementing house sale and purchase agreements based on Indonesian laws and regulations. This article uses a juridical-normative method with a statutory and case approach to examine the legal obligations of developers and legal protection for consumers. In the end, there will be results from the discussion of this article regarding the developer’s responsibilities in house sale and purchase agreements including fulfilling obligations in accordance with Article 1338 of the Civil Code concerning the principle of pacta sunt servanda and Law Number 8 of 1999 concerning Consumer Protection. Consumer protection law provides ample space for consumers to protect their legal rights so that they are not easily harmed by parties who do not comply with the contents of the agreement.